Comparison of Measured Creatinine Clearance and Clearances Estimated by Cockcroft-Gault and MDRD Formulas in Patients with a Single Kidney - Sebastião Rodrigues Ferreira-Filho; Camila Caetano Cardoso; Luiz Augusto Vieira de Castro; Ricardo Mendes Oliveira; Renata Rodrigues Sá (International Journal of Nephrology)
There are doubts about whether the values obtained from the Cockroft-Gault (ClCG) and Modification of Diet in Renal Disease (GFRMDRD) formulas are comparable to the more traditional formula used to obtain the creatinine clearance from a 24-hour urine collection (ClCrm), particularly in patients with only one kidney. The present study aimed to compare these formulas in individuals with one remaining kidney after previous nephrectomy (Nx) and to verify which estimated formula correlates more closely with ClCrm. Thirty-six patients who had undergone Nx had their renal filtration analyzed with ClCG, GFRMDRD and by ClCrm. The average time after Nx was 11.6±9.0 years, and the average age at the time of the study was 50.7±10.6 years old (X ± SD). The results of three clearances were 81.1±35.6 mL·min·m2 for ClCrm, 70.4±24.0mL·min·m2 for ClCrCG, and 71.2±19.2mL·min·m2 for GFRMDRD (with ClCrm > ClCrCG and GFRMDRD; 𝑃<.001). No difference was found between the ClCrCG and GFRMDRD values (𝑃=.72). The data demonstrated that both estimate formulas were strongly correlated with ClCrm, although ClCrCG was more closely associated with ClCrm than GFRMDRD (ClCrCG with 𝑟2∶0.64 and GFRMDRD with 𝑟2∶0.34; 𝑃<.001). In conclusion, for people with only one kidney remaining after NX, our data showed that glomerular filtration rate estimation by ClCrCG is more related to the values obtained with the traditional clearance measurement based on a 24-hour urine collection test.